Poetry and Psychotherapy: the Case for Fernando Pessoa as a Therapist. Poetry as a Tool in Psychotherapy - Erick Messias (The Global Psychotherapist, 2024)
Nossrat Peseschkian incorporated the use of stories as a key element of Positive Psychotherapy (Peseschkian 2016). Poetry has also been proposed as a powerful tool in psychotherapy and defined as “the use of language, symbol and story in therapeutic, educational and community-building capacities.” (Mazza 2016). Among great poets Fernando Pessoa is relatively unknown due to his writing in Portuguese and to the complexity of his multiple styles, personas and perspectives. Yet, this very complexity makes his poetry, alongside his unique prose, powerful tools to be used in psychotherapy. Finally, his poems are easily accessible in both Portuguese and English today. This article starts with a brief biographical introduction to Pessoa, followed by examples of his work under different voices that can be used by mental health professionals in supporting persons in the process of healing through psychotherapy.